2022
DOI: 10.21203/rs.3.rs-2350554/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of Bemisia tabaci MEAM1 on soybean and resistance traits of cultivars

Abstract: This study aimed to evaluate the biological development of Bemisia tabaci MEAM1 confined on eleven soybean cultivars under greenhouse conditions and estimate genetic parameters for correlated resistance traits. Twenty individuals of B. tabaci were released in cages and closed in the petioles of the plant leaflets. A completely randomized design was used with eleven treatments and five replicates. The evaluations occurred over 25 days. The insects that emerged from the bioassay were confined to plants of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The observation that resistant cultivars, demonstrating antixenosis or antibiosis against B. tabaci, exhibit heightened photosynthetic parameters, while susceptible cultivars consistently display reductions, implies that resistance mechanisms play a vital role in sustaining soybean plant photosynthetic efficiency under whitefly infestations. "Antixenosis" refers to characteristics deterring insect settling or feeding, while "antibiosis" negatively impacts insect growth, development, or survival when feeding on the plant [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that resistant cultivars, demonstrating antixenosis or antibiosis against B. tabaci, exhibit heightened photosynthetic parameters, while susceptible cultivars consistently display reductions, implies that resistance mechanisms play a vital role in sustaining soybean plant photosynthetic efficiency under whitefly infestations. "Antixenosis" refers to characteristics deterring insect settling or feeding, while "antibiosis" negatively impacts insect growth, development, or survival when feeding on the plant [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Resistant cultivars may better balance energy allocation for defense mechanisms and growth, contributing to higher photosynthetic efficiency. Additionally, they may produce secondary metabolites in response to whitefly feeding, some positively impacting photosynthesis and overall plant health [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This balance can contribute to higher photosynthetic efficiency. Resistant cultivars might produce secondary metabolites in response to whitefly feeding, and some of these compounds could have positive effects on photosynthesis and overall plant health [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The eleven soybean cultivars were chosen based on prior research, which demonstrated their adaptability to the northeastern Brazilian environment and their ability to yield well. These cultivars can be considered valuable sources of resistance against B. tabaci MEAM1 for breeding programs aimed at developing resistant soybean cultivars [19,20] (Table 1).…”
Section: Soybean Cultivarsmentioning
confidence: 99%